'One vast empire': China, progress, and the Scottish Enlightenment. Issue 1 (2nd January 2018) - Dodds, Phil
ABSTRACT: Although references to China were few and fragmentary, the example of a 'stationary' East Asian Empire featured importantly in Scottish Enlightenment ideas about religion and political economy. David Hume considered whether the apparently long-flourishing system of Chinese government, grounded in rationally deduced deistic ethics, could provide an example for Western nations. Later in the eighteenth century, however, Adam Smith criticized China's 'stationary' state, and demonstrated why Europe should be a model for China. This article explores how Hume and Smith developed their particular understandings of China, focusing on the changing material and intellectual context, and the nature and provenance of the sources they relied on. It argues that Smith's ultimate application of a European (or, perhaps, Scottish) theory of progress to the country that had initially seemed to be the theory's most notable exception should be seen as a key juncture in global intellectual history. Further, the persistent belief that China was a secretive culture that needed to be revealed to European science was a kind of imperial desire for knowledge that should not be separated from the colonizing behaviour of the British in East Asia in the nineteenth century.